PROSES PEMBUATAN KOMPOS 01 RUMAH KOMPOS TENGGILIS MElOYO SURABAYA - Pradana Rony Septyanto; Suparlan .; Marlik . (GEMA LINGKUNGAN KESEHATAN, 2013)
Compos House of Tenggilis Mejoyo is one of Compos Houses managed by DinasKebersihan dan Pertamanan (Cleanliness and Gardening Service) of Surabaya City. ComposHouse of Tenggilis Mejoyo Is a Compos House processing organic garbage (leaves) in whichmostly comes from city gardens and suburban roads. The aim of the research is to recognizecompos manufacturing process in Compos House of Tenggills Mejoyo, Surabaya.This research is a descriptive one, namely describing the actual condition of objectsobserved. Whereas the questioned objects include raw material size, stirring, humidity,temperature measuring, acidity level (pH), raw material ratio CIN measurement, compostingprocessing time, and physical compos production.The research observed that the average compos raw material was 0.7-2 em height;compos stirring was conducted approximately every 3-4 days; composting course was 27days; CfN raw material ratio was 30.14, and C/N compos ratio was 11.66; compos humiditywas approxtmatelv 45% - 80% with initial and final composting humidity were 79% and 57%,respectively; composting temperature was approximately 29°C-75°C, with initial and finaleomposting temperature of 30°C and 65°C, respectively; initial and final composting pH were6.5 and 7.5; the color of mature compos is similar to soil and odorless.Therefore, it is suggested for Compos House of Tenggilis Mejoyo Surabaya to performa more routine composting process stirring time, minimal every day, and to measure, and usethe APD.